SOCIAL SUPPORT AS A MODERATOR IN THE RELATIONSHIP BETWEEN WORKLOAD AND INTENTION TO QUIT AMONG CONTRACT EMPLOYEES: A MODERATED REGRESSION ANALYSIS - Fatwa Zuhaena (JURNAL ILMIAH EDUNOMIKA, 2020)
This study investigates the moderating role of social support in the relationship between workload and intention to quit among contract employees of manufacturing companies in Cilacap Regency, Central Java, Indonesia. Grounded in the Job Demands-Resources (JD-R) Model (Demerouti et al., 2001) and Social Support Theory (House, 1981), this research employs a quantitative approach using moderated regression analysis. Data were collected from 132 contract employees across six manufacturing firms using purposive sampling. Structured questionnaires with a five-point Likert scale were employed for data collection. The results reveal that workload significantly and positively predicts intention to quit (β = 0.408, p < 0.001), while social support significantly and negatively predicts intention to quit (β = −0.369, p < 0.001). Critically, social support significantly moderated the relationship between workload and intention to quit (β = −0.234, p < 0.01), such that the positive effect of workload on intention to quit was substantially weaker when social support was high. These findings advance the understanding of buffer mechanisms in the relationship between workload and quit intention and offer actionable implications for contract employee management in Indonesian manufacturing settings. Keywords: workload, intention to quit, social support, moderation, contract employees, JD-R model, manufacturing